Investigating the effect of roasting on robusta (Coffea caniphora) coffee beans from Sarangani Province, Philippines using nuclear magnetic resonance (NMR) spectroscopy - Lacaden-Bautista, Mialo C (2024.)
In recent years, the focus of extensive coffee research is on coffee compounds that have many health benefits such as caffeine, trigonelline, and chlorogenic acids. The chemical composition, organoleptic properties, and physico-chemical properties of coffee beans may be affected by many factors, such as temperature and time of roasting. Hence, this study aimed to evaluate the impact of roasting on process-induced quality changes of Robusta coffee (Coffea canephora) beans from Malungon, Sarangani Province, Philippines using Nuclear Magnetic Resonance (NMR) Spectroscopy. The variable in this study is roasting time (0, 9, 14, 18, 24, 28, and 33 minutes) while the parameters measured were moisture content, water activity, total titratable acids, pH, total dissolved solids, and coffee compounds. One-ay ANOVA (p<0.05) withpost-hoc Tukey;s test revealed that brews from Robusta coffee beans roasted for 9 and 14 minutes were significantly acidic and had the most titratable acids and dissolved solids among other brews. There were 9 monitoring coffee compounds identified in the ¹H-NMR spectra (HMF, trigolline, caffeine, N-methylpyridium, sucrose, formic acid, lactic acid, acetic acid, and 5-CQA) using Bruker Topsin 4.3 software. Gaussian linear model (GLM) was used to select chemical shifts (integral value) of monitoring compounds to be used in the multivariate analysis of the coffee compounds through the increasing coffee bean roasting times. Principal component analysis - biplot of the ration concentrations (integral value) of 7 monitoring compounds revealed that coffee beans roasted for 9 and 14 minutes contain the most amount of trigonelline, chlorogenic acids, caffeine and aliphatic acids. Meanwhile, brews from coffee beans roasted for 24, 28 and 33 minutes had the most amount of N-methlpyridium. The results in this study would benefit the Philippines Robusta coffee growers and roasters.
Thesis (M.S. Food Science) -- [Miagao, Iloilo] : University of the Philippines Visayas, July 2024.